Pengaruh Enterpreneur Skills dan Pemanfaatan Peluang Usaha terhadap Minat Usaha Di Kabupaten Purwakarta - Sopian, Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the influence of entrepreneurial skills and business opportunities on business interest in Purwakata district. People's interest in business in developing countries is not very high, this happens because people in developing countries prefer to work rather than entrepreneurship. People assume that it is more profitable to work than entrepreneurship, especially in communities around industrial cities which are companies that are expanding from developed countries. The research method used is an associative descriptive method with a quantitative approach. The type of data used is primary data by distributing questionnaires to respondents where the respondents are from the Purwakarta district community. The research results show that there is a positive and significant influence between entrepreneurial skills and business opportunities on business interest in Purwakarta district, both partially and simultaneously. Descriptively, weaknesses in entrepreneurial skills are based on incentives, ability measurement, personal potential, technological abilities and in the business opportunity aspect there are weaknesses in family support, business networks and opportunities for new ideas and in the business interest aspect there are weaknesses in interest, risks and challenges.